Healthy Birth Practice #4: Avoid Interventions Unless They Are Medically Necessary - Lothian, Judith A. (J Perinat Educ, 2019)
Maternity care in the United States continues to be intervention intensive. The routine use of intravenous fluids, restrictions on eating and drinking, continuous electronic fetal monitoring, epidural analgesia, and augmentation of labor characterize most U.S. births. The use of episiotomy has decreased but is still higher than it should be. These interventions disturb the normal physiology of labor and birth and restrict women's ability to cope with labor. The result is a cascade of interventions that increase risk, including the risk of cesarean surgery, for women and babies. This paper describes the use and effect of routine interventions on the physiologic process of labor and birth and identifies the unintended consequences resulting from the routine use of these interventions in labor and birth.